Financial Sector Assessment : Sri Lanka - World Bank (2012)
This Financial Sector Assessment (FSA) is based on the work of the joint World Bank and IMF Financial Sector Assessment Program (FSAP) update team that visited Sri Lanka between June 20 and July 3, 2007. The principal objectives of the FSAP Update were to: (i) assess developments in the financial sector and progress in strengthening financial sector regulation since 2002; and (ii) identify measures that would contribute to consolidation of financial stability and to further development of the financial sector over the next five years. This report describes the main findings of the 2007 FSAP update addressing bank and non bank financial institutions, state bank restructuring, pension funds, insurance, capital markets, supervisory framework, access to finance, and legal and judicial reforms. This report summarizes the recommendations for sustaining financial development.